Negative electrode and battery

By using the mixture of phosphorus carbon composite materials and graphite in phosphorus carbon batteries, the expansion and processing performance problems of phosphorus carbon batteries are solved, and high energy and high power performance are achieved, and the safety performance of the battery is improved.

CN119153621APending Publication Date: 2024-12-17TSINGHUA UNIVERSITY +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202310717027.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Phosphorus carbon batteries are prone to expand at high temperatures and have poor processing performance of the pole sheet, which affects the battery cycle life and safety performance.

Method used

The composite negative electrode material is prepared by mixing phosphorus carbon composite materials with graphite and other carbon materials, and the composite negative electrode material is prepared by high-temperature adsorption method or high-energy ball milling method, and stirring and mixing with conductive agent and binder to produce a battery slurry containing composite negative electrode material. The coating thickness is controlled during the preparation of the pole sheet to improve the cycling performance and volume expansion performance of the battery.

Benefits of technology

It significantly improves the circulation performance and volume expansion problems of phosphorus-carbon system batteries, avoids the precipitation of "lithium dendrites", and improves the safety performance and processing performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153621A_ABST
    Figure CN119153621A_ABST
Patent Text Reader

Abstract

According to the negative electrode and the battery, an active material in the negative electrode is a composite negative electrode material and comprises a phosphorus-carbon composite material and a carbon material, and the mass percent of the phosphorus-carbon composite material is greater than or equal to 50%. By mixing the phosphorus-carbon composite material with carbon materials such as graphite for use, the cycle performance of a phosphorus-carbon system battery can be greatly improved, and the problem of volume expansion can be solved, so that the lithium ion battery can effectively give consideration to high energy and high power performance, and precipitation of lithium dendrites on the surface of a negative electrode can be effectively avoided to a certain extent; and the safety performance of the battery is greatly improved. Furthermore, the addition of the carbon material is beneficial to improving the processing performance of the phosphorus-carbon negative electrode plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present invention relate to the field of battery technology, and in particular to a negative electrode and a battery. Background Art

[0002] With the emergence of emerging markets such as electric vehicles (EV) and hybrid electric vehicles (HEV), there is a huge demand for lithium-ion batteries (LIB). As one of the core materials of lithium-ion batteries for new energy vehicles, negative electrode materials play a vital role in the final performance of new energy vehicles. Silicon-based negative electrode materials have been well applied in high energy density batteries in recent years due to their extremely high theoretical lithium storage capacity (4200mAh / g) and low lithium desorption potential. However, in the production process of silicon-based batteries, a large amount of fluoroethylene carbonate (FEC) is used in the matching electrolyte. The electrolyte is easily decomposed to generate HF at high temperature, which affects the high temperature performance of the battery and is harmful to the environment. In addition, the expansion of silicon-based negative electrode materials is very high, which has always been a difficult problem to be solved in the industry. As another emerging negative electrode material, phosphorus-based negative electrode has the advantages of low price, abundant reserves, environmental friendliness, and high specific capacity, and has gradually developed into the focus of negative electrode research.

[0003] Phosphorus-based battery electrolytes do not require FEC, and there is no problem of decomposition to generate HF at high temperatures; however, although the expansion of the phosphorus-carbon composite negative electrode material formed by the combination of phosphorus-based negative electrode materials and carbon has been greatly improved, it will still produce a large volume deformation when used in a full battery, which can easily cause poor contact between the active material and the conductive agent and current collector, thereby causing the battery capacity to decay rapidly and affecting the battery's cycle life; and during the coating process of the electrode, the coating thickness is too thin due to its high gram capacity, which is not conducive to processing and manufacturing.

[0004] Therefore, how to optimize the volume expansion and electrode processing performance of phosphorus-carbon batteries has become a technical problem that technical personnel in this field need to solve urgently. Summary of the invention

[0005] The technical problem solved by the embodiments of the present invention is to improve the expansion and pole piece processing performance of phosphorus-carbon batteries.

[0006] To solve the above problems, an embodiment of the present invention provides a negative electrode, wherein the active material in the negative electrode is a composite negative electrode material, including a phosphorus-carbon composite material and a carbon material, and the mass percentage of the phosphorus-carbon composite material is greater than or equal to 50%.

[0007] Optionally, the carbon material is graphite.

[0008] Optionally, the median particle size of the graphite is in the range of 6 μm to 20 μm.

[0009] Optionally, the mass percentage of active material in the negative electrode is 70% to 98%.

[0010] Optionally, the current collector used in the negative electrode is one of copper foil, aluminum foil or carbon-coated aluminum foil.

[0011] Optionally, the composite negative electrode material is prepared by one or a combination of the following methods:

[0012] First, phosphorus and porous carbon are compounded by high-temperature adsorption method or high-energy ball milling method to obtain phosphorus-carbon material; then the phosphorus-carbon material is physically mixed with graphite to obtain a composite negative electrode material; then the composite negative electrode material, conductive agent, binder and solvent are stirred and mixed to obtain a battery slurry containing the composite negative electrode material;

[0013] First, the porous carbon material graphite is physically mixed to obtain a composite carbon material; then phosphorus and the composite carbon material are compounded by a high-temperature adsorption method or a high-energy ball milling method to obtain a composite negative electrode material; then the composite negative electrode material, a conductive agent, a binder and a solvent are stirred and mixed to obtain a battery slurry containing the composite negative electrode material;

[0014] First, phosphorus and porous carbon are compounded by high-temperature adsorption method or high-energy ball milling method to obtain phosphorus-carbon material; then, in the negative electrode slurry preparation stage, the phosphorus-carbon material and graphite are added to a disperser in sequence, and then a conductive agent, a binder and a solvent are added according to a certain process and stirred and mixed, thereby obtaining a battery slurry containing a composite negative electrode material.

[0015] Optionally, the coating thickness of the battery slurry is less than or equal to 48 mg / cm 2 .

[0016] Optionally, the binder used in the negative electrode is one or a combination of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.

[0017] To solve the above problems, an embodiment of the present invention further provides a battery, comprising a positive electrode, a separator, an electrolyte and the above-mentioned negative electrode.

[0018] Optionally, the active material in the positive electrode is one or a combination of nickel-cobalt-manganese or nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel oxide.

[0019] Optionally, the diaphragm is at least one of a polyethylene film, a polypropylene film, a polypropylene / polyethylene / polypropylene composite film, and a nylon cloth.

[0020] Compared with the prior art, the technical solution of the embodiment of the present invention has the following advantages:

[0021] The negative electrode provided by the embodiment of the present invention comprises a negative electrode active material including a phosphorus-carbon composite material and a carbon material, wherein the mass ratio of the phosphorus-carbon composite material is greater than or equal to 50%. By mixing the phosphorus-carbon composite material with carbon materials such as graphite, the cycle performance of the phosphorus-carbon system battery can be greatly improved and the volume expansion problem can be improved, so that the lithium-ion battery can effectively take into account both high energy and high power performance, and to a certain extent, it can also effectively avoid the precipitation of "lithium dendrites" on the negative electrode surface, greatly improving the safety performance of the battery. Furthermore, the addition of carbon materials is conducive to improving the processing performance of the phosphorus-carbon negative electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0023] Figure 1 It is a battery cycle comparison diagram of Examples 1-3 of the present invention and the comparative example;

[0024] Figure 2 It is a comparison chart of battery volume expansion of Examples 1-3 of the present invention and the comparative example. DETAILED DESCRIPTION

[0025] Terms and Definitions

[0026] PVDF-Polyvinylidene fluoride CMC-Sodium carboxymethyl cellulose

[0027] SBR-Styrene Butadiene Rubber PAA-Acrylic Acid Homopolymer

[0028] PAA-Na-Sodium Polyacrylate PAA-Li-Lithium Polyacrylate

[0029] As can be seen from the background technology, the volume expansion problem and electrode processing performance of phosphorus-carbon batteries need to be improved.

[0030] To solve the above problems, an embodiment of the present invention provides a negative electrode, wherein the active material in the negative electrode is a composite negative electrode material, including a phosphorus-carbon composite material and a carbon material, and the mass percentage of the phosphorus-carbon composite material is greater than or equal to 50%.

[0031] Phosphorus-carbon composite materials refer to phosphorus / carbon composite materials prepared by sublimation condensation method, high temperature adsorption method or high temperature ball milling method.

[0032] The composite negative electrode material refers to a secondary composite of a phosphorus-carbon composite material and a carbon material, and the composite method is a common physical mixing method. The carbon material can be at least one of graphite, soft carbon, and hard carbon.

[0033] Taking graphite as an example, in order to improve the expansion performance of the battery while ensuring the battery energy density, the mass percentage of the phosphorus-carbon composite material in the composite negative electrode material is controlled to be greater than or equal to 50%, that is, the mass percentage of graphite is less than or equal to 50%. For example, the mass ratio of the phosphorus-carbon composite material to graphite can be 5:5, 4:6, 3:7, 8:2, 9:1.

[0034] In order to further improve the processing performance of the negative electrode sheet and improve the volume expansion of the battery, the particle size of the graphite can range from 6 μm to 20 μm, further, 13 μm to 17 μm, for example, 14 μm, 15 μm, 16 μm. The particle size refers to the median particle size D50 of the graphite.

[0035] In order to improve the energy density of the battery while ensuring the bonding effect and conductive effect of the pole piece, the mass percentage of the active material in the negative electrode can be 70% to 98%. For example, the mass percentage of the active material can be 75%, 80%, 85%, 90%, 91%, 92%, 93%, 94%, 95%, etc. By adding carbon materials such as graphite to the phosphorus-carbon composite material, the amount of adhesive can be reduced, thereby increasing the content of active materials and the energy density of the battery. Moreover, after adding carbon materials such as graphite, the specific surface area of ​​the phosphorus-carbon composite material can be reduced, and the dispersion is more uniform.

[0036] The current collector used in the negative electrode is one of copper foil, aluminum foil or carbon-coated aluminum foil.

[0037] The composite negative electrode material is prepared by one or a combination of the following methods:

[0038] First, phosphorus and porous carbon are compounded by high-temperature adsorption method or high-energy ball milling method to obtain phosphorus-carbon material; then the phosphorus-carbon material is physically mixed with carbon material to obtain composite negative electrode material; then the composite negative electrode material, conductive agent, binder and solvent are stirred and mixed to obtain battery slurry containing composite negative electrode material;

[0039] First, the porous carbon material and the carbon material are physically mixed to obtain a composite carbon material; then, phosphorus is compounded with the composite carbon material by a high-temperature adsorption method or a high-energy ball milling method to obtain a composite negative electrode material; then, the composite negative electrode material, a conductive agent, a binder and a solvent are stirred and mixed to obtain a battery slurry containing the composite negative electrode material;

[0040] First, phosphorus and porous carbon are compounded by high-temperature adsorption method or high-energy ball milling method to obtain phosphorus-carbon material; then, in the negative electrode slurry preparation stage, the phosphorus-carbon material and carbon material are added to a disperser in sequence, and then a conductive agent, a binder and a solvent are added according to a certain process and stirred and mixed, thereby obtaining a battery slurry containing a composite negative electrode material.

[0041] The coating thickness of the battery slurry is less than or equal to 48 mg / cm 2 The addition of graphite can improve the leakage of pure phosphorus carbon negative electrode sheets caused by over-thin coating, making the coating thickness of negative electrode slurry as high as 48mg / cm 2 , so it is not easy to leak foil.

[0042] The binder used in the negative electrode is one or a combination of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.

[0043] The negative electrode provided in the embodiment of the present invention, the negative electrode active material includes a phosphorus-carbon composite material and a carbon material, wherein the mass ratio of the phosphorus-carbon composite material is greater than or equal to 50%. By mixing the phosphorus-carbon composite material with carbon materials such as graphite, the cycle performance of the phosphorus-carbon system battery can be greatly improved and the volume expansion problem can be improved. Furthermore, the addition of carbon materials is conducive to improving the processing performance of the phosphorus-carbon negative electrode sheet. It can be seen that the negative electrode provided in the embodiment of the present invention, the lithium-ion battery can effectively take into account both high energy and high power performance, and to a certain extent can also effectively avoid the precipitation of "lithium dendrites" on the negative electrode surface, greatly improving the safety performance of the battery.

[0044] To solve the above problems, an embodiment of the present invention further provides a battery, comprising a positive electrode, a separator, an electrolyte and the above-mentioned negative electrode. The battery comprises an ion insertion and extraction battery, specifically, the ions can be metal ions such as lithium ions, zinc ions, magnesium ions, etc., such as a lithium ion battery.

[0045] In an embodiment of the present invention, the active material in the positive electrode is one or a combination of nickel-cobalt-manganese or nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel oxide.

[0046] In an embodiment of the present invention, the diaphragm is one of a polyethylene film, a polypropylene film, a polypropylene / polyethylene / polypropylene composite film, a nylon cloth, a polyethylene film, a polyimide film, a polyethylene terephthalate, a cellulose film, a polyamide film, a poly(p-phenylene terephthalamide) film and a polyurethane fiber film.

[0047] Specifically, the polypropylene / polyethylene / polypropylene composite film (PP / PE / PP) includes at least one of the following situations:

[0048] PP / PE / PP composite film, without coating;

[0049] PP / PE / PP composite film, with nano-alumina coating on one or both sides;

[0050] PP / PE / PP composite film with single or double-sided adhesive coating;

[0051] PP / PE / PP composite film, with single or double-sided coating of nano-aluminum oxide and glue.

[0052] The glue coating can be PVDF, SBR, PAANa or LA132.

[0053] In an embodiment of the present invention, the electrolyte in the electrolyte includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(oxalato)borate, lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI); the solvent in the electrolyte is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate; the additive in the electrolyte includes at least one of vinylene carbonate, propane sultone, carboxylates, succinonitrile and adiponitrile.

[0054] In the battery provided by the embodiment of the present invention, the active material of the negative electrode sheet includes a phosphorus-carbon composite material and a carbon material, wherein the mass ratio of the phosphorus-carbon composite material is greater than or equal to 50%. By mixing the phosphorus-carbon composite material with carbon materials such as graphite, the cycle performance of the phosphorus-carbon system battery can be greatly improved and the volume expansion problem can be improved, so that the lithium-ion battery can effectively take into account both high energy and high power performance, and to a certain extent, it can also effectively avoid the precipitation of "lithium dendrites" on the negative electrode surface, greatly improving the safety performance of the battery. Furthermore, the addition of carbon materials is conducive to improving the processing performance of the phosphorus-carbon negative electrode sheet.

[0055] The negative electrode and the battery of the present invention are further described in detail below in conjunction with specific embodiments and comparative examples.

[0056] Example 1

[0057] Preparation process of phosphorus-carbon composite materials:

[0058] Phosphorus and porous carbon (mass ratio 1:1) are compounded by high temperature adsorption method or high energy ball milling method to prepare phosphorus-carbon composite material;

[0059] The ratio parameters of the negative electrode raw materials are: the mass percentage of the mixed material of phosphorus-carbon composite material and graphite is 89%-94%, the total mass percentage of the conductive agent composed of conductive carbon black and carbon nanotubes is 3%-6%, and the binder (PAALi or PAANa is 3%-5% by mass).

[0060] Negative electrode slurry preparation:

[0061] Step a): adding conductive carbon black into CMC solution to prepare a conductive slurry;

[0062] Step b): adding the phosphorus-carbon composite material and graphite in a mass ratio of 9:1 to the conductive slurry in step a), adding an appropriate amount of water solvent to adjust the solid content to 45%, and continuing stirring for 5 hours;

[0063] Step c): adding PAALi or PAANa to the slurry of step b) and stirring for 1 hour, degassing for 30 minutes under slow stirring, and obtaining a negative electrode slurry for a lithium-ion battery after drying.

[0064] Pole sheet preparation: The negative electrode slurry is coated on a copper foil with a thickness of 8 μm. The coating thickness on one side of the negative electrode sheet is 32 mg / cm 2 , the foil is not easy to expose, and the negative electrode sheet is obtained after coating, rolling, cutting and baking.

[0065] The positive electrode (active material (Li (Ni 0.6 Co 0.2 Mn 0.2 )O2)), the separator (PP / PE / PP) and the negative electrode sheet are assembled, encapsulated with an aluminum-plastic film, injected with electrolyte (lithium hexafluorophosphate), and prepared into a battery through chemical formation, ultimately forming a soft-pack battery.

[0066] Example 2

[0067] The difference between Example 2 and Example 1 lies in the negative electrode step b): adding the phosphorus-carbon composite material and graphite to the conductive slurry in step a) at a ratio of 7:3, adding an appropriate amount of water solvent to adjust the solid content to 45%, and continuing stirring for 5 hours; the negative electrode sheet single-sided coating thickness is 40 mg / cm 2 , the rest is the same as in Example 1.

[0068] Example 3

[0069] The difference between Example 3 and Example 1 lies in the negative electrode step b): adding the phosphorus-carbon composite material and graphite to the conductive slurry in step a) at a ratio of 5:5, adding an appropriate amount of water solvent to adjust the solid content to 45%, and continuing stirring for 5 hours; the negative electrode sheet single-sided coating thickness is 48 mg / cm 2 , the rest is the same as in Example 1.

[0070] Comparative Example:

[0071] The ratio parameters of the negative electrode raw materials are: the total content of phosphorus-carbon composite material is 89%-94%, the total mass percentage of the conductive agent composed of conductive carbon black and carbon nanotubes is 3%-6%, and the binder (PAALi or PAANa ranges from 3% to 5%).

[0072] Negative electrode slurry preparation:

[0073] Step a): adding conductive carbon black into CMC solution to prepare a conductive slurry;

[0074] Step b): adding a phosphorus-carbon composite material (phosphorus to porous carbon mass ratio of 1:1) to the conductive slurry in step a), adding an appropriate amount of water solvent to adjust the solid content to 45%, and continuing stirring for 5 hours;

[0075] Step c): adding PAALi or PAANa to the slurry of step b) and stirring for 1 hour, degassing for 30 minutes under slow stirring, and obtaining a negative electrode slurry for a lithium-ion battery after drying.

[0076] Pole sheet preparation: The negative electrode slurry is coated on a copper foil with a thickness of 8 μm. The coating thickness on one side of the negative electrode sheet is 28 mg / cm 2 , the foil is easily exposed, and the negative electrode sheet is obtained after coating, rolling, cutting, baking and baking.

[0077] The positive electrode (active material (Li (Ni 0.6 Co 0.2 Mn 0.2 )O2)), the separator (PP / PE / PP) and the negative electrode sheet are assembled, encapsulated with an aluminum-plastic film, injected with electrolyte (lithium hexafluorophosphate), and prepared into a battery through chemical formation, ultimately forming a soft-pack battery.

[0078] During the processing of the negative electrode sheet, the negative electrode slurry of Examples 1-3 has a single-sided coating thickness of 32 mg / cm 2 -48mg / cm 2 , not easy to leak foil; while the negative electrode slurry coating thickness on one side of the comparative example is 28mg / cm 2 , and the foil is prone to leaking; this shows that adding graphite to the phosphorus-carbon composite material can indeed improve the processing performance of the phosphorus-carbon negative electrode sheet.

[0079] The relevant performances of the batteries prepared in Examples 1-3 and the comparative example were tested respectively, including the room temperature cycle performance and the full-charge thickness expansion. The specific test methods are as follows:

[0080] (1) Room temperature cycle performance test: At 25°C, the formed battery is charged to 4.3V with a constant current and constant voltage of 0.1C (cut-off current is 0.01C), and then discharged to 1.0V with a constant current of 0.1C. The capacity retention rate after 100 cycles of charge / discharge is calculated as follows:

[0081] Capacity retention rate after 100 cycles (%) = 100th cycle discharge capacity / 1st cycle discharge capacity × 100%.

[0082] The performance test results of the lithium ion batteries prepared in the above examples 1-3 and the comparative example are as follows: Figure 1 shown.

[0083] Depend on Figure 1 It can be seen that with the increase of graphite addition, the battery cycle performance is getting better and better.

[0084] (2) Full-charge thickness expansion test: At 25°C, charge the formed battery to 4.3V using 0.1C constant current and constant voltage (cut-off current is 0.01C), measure the thickness of the battery after charging, and then discharge it to 1.0V using 0.1C constant current, and measure the thickness of the battery after discharging.

[0085] Battery expansion rate (%) = (thickness of fully charged battery - thickness of discharged battery) / thickness of battery before full charge × 100%.

[0086] The expansion rates of the lithium ion batteries prepared in the above Examples 1-3 and Comparative Examples are as follows: Figure 2 shown.

[0087] Depend on Figure 2 It can be seen that the expansion rate of Example 1 is 10%, the expansion rate of Example 2 is 5%, the expansion rate of Example 3 is 3%, and the expansion rate of the comparative example is 12%. It can be seen that mixing graphite in different proportions does have a good effect on improving the expansion of the battery.

[0088] Furthermore, during the charge and discharge process, no lithium dendrites were found in the negative electrodes of Examples 1-3, while lithium dendrites were clearly found in the comparative example.

[0089] In summary, the negative electrode and battery of the present application can greatly improve the cycle performance of the phosphorus-carbon system battery and improve the volume expansion problem by mixing the phosphorus-carbon composite material with carbon materials such as graphite, so that the lithium-ion battery can effectively take into account both high energy and high power performance, and to a certain extent, it can also effectively avoid the precipitation of "lithium dendrites" on the negative electrode surface, greatly improving the safety performance of the battery. Furthermore, the addition of carbon materials is conducive to improving the processing performance of the phosphorus-carbon negative electrode sheet.

[0090] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A negative electrode, characterized in that: The active material in the negative electrode is a composite negative electrode material, including a phosphorus-carbon composite material and a carbon material, and the mass percentage of the phosphorus-carbon composite material is greater than or equal to 50%.

2. The negative electrode according to claim 1, characterized in that The carbon material is graphite.

3. The negative electrode according to claim 2, characterized in that: The median particle size of the graphite is in the range of 6 μm to 20 μm.

4. The negative electrode according to claim 1, characterized in that: The mass percentage of active material in the negative electrode is 70% to 98%.

5. The negative electrode according to claim 1, characterized in that: The current collector used in the negative electrode is one of copper foil, aluminum foil or carbon-coated aluminum foil.

6. The negative electrode according to claim 2, characterized in that: The composite negative electrode material is prepared by one or a combination of the following methods: First, phosphorus and porous carbon are compounded by high-temperature adsorption method or high-energy ball milling method to obtain phosphorus-carbon material; then the phosphorus-carbon material is physically mixed with graphite to obtain a composite negative electrode material; then the composite negative electrode material, conductive agent, binder and solvent are stirred and mixed to obtain a battery slurry containing the composite negative electrode material; First, the porous carbon material and graphite are physically mixed to obtain a composite carbon material; then, phosphorus and the composite carbon material are compounded by a high-temperature adsorption method or a high-energy ball milling method to obtain a composite negative electrode material; then, the composite negative electrode material, a conductive agent, a binder and a solvent are stirred and mixed to obtain a battery slurry containing the composite negative electrode material; First, phosphorus and porous carbon are compounded by high-temperature adsorption method or high-energy ball milling method to obtain phosphorus-carbon material; then, in the negative electrode slurry preparation stage, the phosphorus-carbon material and graphite are added to a disperser in sequence, and then a conductive agent, a binder and a solvent are added according to a certain process and stirred and mixed, thereby obtaining a battery slurry containing a composite negative electrode material.

7. The negative electrode according to claim 6, characterized in that The coating thickness of the battery slurry is less than or equal to 48 mg / cm 2 .

8. The negative electrode according to any one of claims 1 to 7, characterized in that: The binder used in the negative electrode is one or a combination of PVDF, CMC, SBR, PAA, PAA-Na, and PAA-Li.

9. A battery, characterized in that: The invention comprises a positive electrode, a separator, an electrolyte and a negative electrode as claimed in any one of claims 1 to 8.

10. The battery according to claim 9, characterized in that The active material in the positive electrode is one or a combination of nickel-cobalt-manganese or nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese oxide, lithium cobalt oxide, and lithium nickel oxide.

11. The battery according to claim 9, characterized in that The diaphragm is at least one of a polyethylene film, a polypropylene film, a polypropylene / polyethylene / polypropylene composite film, and a nylon cloth.

Citation Information

Cited By

  • Preparation method of secondary battery with high energy density and high safety

    CN119695293A

  • Negative plate, preparation method thereof and lithium ion secondary battery

    CN119993987A

  • Negative electrode sheet, method for manufacturing the same, and lithium-ion secondary battery

    CN119993987B